From the physical learning spaces to the virtual classroom: the role of the teacher in the digitization era - Rosanna Tammaro; Deborah Gragnaniello; Roberta Scarano (Firenze University Press, 2022)
In educational contexts, a careful space planning where the training process takes place is indispensable because it promotes changes and innovation and inclusion processes. With the distance learning the design of educational contexts is even more important: online learning environments have peculiar characteristics and, therefore, a simple transposition of traditional practices into virtual environments is not possible. Teaching professionalism and initial and in service training on digital competence and on the inclusion of pupils in virtual educational spaces are fundamental. Therefore, in this article we reflect on the characteristics of the physical and virtual educational spaces and on the role of the teacher in the new educational scenarios.   Dagli spazi educativi fisici all'aula virtuale: il ruolo del docente nell'era della digitalizzazione. Nei contesti educativi, è indispensabile un'attenta progettazione dello spazio in cui si realizza il processo di insegnamento-apprendimento perché esso promuove cambiamenti e processi di innovazione e inclusione. Con la didattica a distanza, la progettazione dei contesti educativi è ancora più importante: gli ambienti di apprendimento online presentano caratteristiche peculiari e, pertanto, non è possibile una semplice trasposizione delle pratiche tradizionali negli ambienti virtuali. La professionalità docente e la formazione, iniziale e continua, sulle competenze digitali e sull'inclusione dei discenti negli spazi educativi virtuali sono fondamentali. Pertanto, in questo articolo riflettiamo sulle caratteristiche degli spazi educativi fisici e virtuali e sul ruolo del docente nei nuovi scenari educativi.